Bioinspired Tough Solid‐State Electrolyte for Flexible Ultralong‐Life Zinc–Air Battery. Issue 18 (3rd April 2022) - Dou, Haozhen; Xu, Mi; Zheng, Yun; Li, Zhaoqiang; Wen, Guobin; Zhang, Zhen; Yang, Leixin; Ma, Qianyi; Yu, Aiping; Luo, Dan; Wang, Xin; Chen, Zhongwei
Abstract: Manufacturing advanced solid‐state electrolytes (SSEs) for flexible rechargeable batteries becomes increasingly important but remains grand challenge. The sophisticated structure of robust animal dermis and good water‐retention of plant cell in nature grant germane inspirations for designing high‐performance SSEs. Herein, tough bioinspired SSEs with intrinsic hydroxide ion (OH − ) conduction are constructed by in situ formation of OH − conductive ionomer network within a hollow‐polymeric‐microcapsule‐decorated hydrogel polymer network. By virtue of the bioinspired design and dynamic dual‐penetrating network structure, the bioinspired SSEs simultaneously obtain mechanical robustness with 1800% stretchability, good water uptake of 107 g g −1 and water retention, and superhigh ion conductivity of 215 mS cm −1 . The nanostructure of bioinspired SSE and related ion‐conduction mechanism are revealed and visualized by molecular dynamics simulation, where plenty of compact and superfast ion‐transport channels are constructed, contributing to superhigh ion conductivity. As a result, the flexible solid‐state zinc–air batteries assembled with bioinspired SSEs witness high power density of 148 mW cm −2, specific capacity of 758 mAh g −1 and ultralong cycling stability of 320 h as well as outstanding flexibility. The bioinspired methodology and deep insight of ion‐conduction mechanism will shed light on the design of advanced SSEs for flexible energy conversion and storage systems. Abstract : A tough, intrinsic hydroxide‐conductive, bioinspired solid‐state electrolyte is designed for flexible ultralong‐life zinc–air batteries, which is featured of dynamic dual‐penetrating network structure with the synergism of ionomer and molecular polymer and gracefully obtains excellent comprehensive properties of mechanical robustness, high ion conductivity and good water retention.